Oyster and Barnacle Recruitment Dynamics on and Near a Natural Reef in China: Implications for Oyster Reef Restoration - Jiang, Wei; Shi, Wen-Jing; Li, Nan-Nan; Fan, Rui-Liang; Zhang, Wen-Kao; Quan, Wei-Min (Frontiers in Marine Science, 2022)
Oysters and barnacles are dominant inhabitants of natural and restored oyster reefs around the world, and high areal coverage of barnacles at natural or restored reefs commonly decreases substrate accessibility for oyster settlement. The overall understanding of oyster and barnacle recruitment dynamics provides invaluable information on site selection and strategies employed for oyster reef restoration. This study documented the temporal and spatial patterns of oyster and barnacle recruitment on and near the largest natural intertidal oyster reef (Liyashan) in China during 2019–2020. The oyster Crassostrea sikamea recruitment appeared as a continuous process from June through late November or early December, with the peak in August. Greater recruits of oyster spat occurred on the sheltered inshore at the upstream of the natural oyster reef than on the reef and the nearby open coast (p < 0.05). The barnacle recruitment extended from spring to early winter, with mid-spring and mid-summer peaks. Conversely, higher barnacle recruitment appeared on the natural oyster reef and the nearby open coast than on the sheltered inshore. Across all the monitoring sites, the cumulative recruits of oysters in each of 2019 and 2020 was negatively correlated with those of barnacles (p < 0.05). The inshore sites (SH1 and SH2) with high oyster recruitment and low barnacle recruitment should be recognized as the natural spatfall sites for the natural oyster reef restoration. The separation in the recruitment peak between the oyster and the barnacle indicated that August was the most favorable window for capturing oyster spat through substratum addition to the water around the natural reef.